The Silene latifolia genome and its giant Y chromosome - Moraga, Carol; Branco, Catarina; Rougemont, Quentin; Jedlička, Pavel; Mendoza-Galindo, Eddy; Veltsos, Paris; Hanique, Melissa; Rodríguez de la Vega, Ricardo C; Tannier, Eric; Liu, Xiaodong; Lemaitre, Claire; Fields, Peter D; et al. (Science (New York, N.Y.), 2025)
In many species with sex chromosomes, the Y is a tiny chromosome. However, the dioecious plant Silene latifolia has a giant ~550-megabase Y chromosome, which has remained unsequenced so far. We used a long- and short-read hybrid approach to obtain a high-quality male genome. Comparative analysis of the sex chromosomes with their homologs in outgroups showed that the Y is highly rearranged and degenerated. Recombination suppression between X and Y extended in several steps and triggered a massive accumulation of repeats on the Y as well as in the nonrecombining pericentromeric region of the X, leading to giant sex chromosomes. Using sex phenotype mutants, we identified candidate sex-determining genes on the Y in locations consistent with their favoring recombination suppression events 11 and 5 million years ago.
Keywords: chromozomy rostlin; rostlinné geny; rekombinace genetická; genom rostlinný; Silene; Genes, Plant; Chromosomes, Plant; Y Chromosome; Genome, Plant; repetitivní sekvence nukleových kyselin; Recombination, Genetic; Repetitive Sequences, Nucleic Acid; chromozom Y